A theoretical review on electronic, magnetic and optical properties of silicene. (18th October 2016) - Chowdhury, Suman; Jana, Debnarayan
Abstract: Inspired by the success of graphene, various two dimensional (2D) structures in free standing (FS) (hypothetical) form and on different substrates have been proposed recently. Silicene, a silicon counterpart of graphene, is predicted to possess massless Dirac fermions and to exhibit an experimentally accessible quantum spin Hall effect. Since the effective spin–orbit interaction is quite significant compared to graphene, buckling in silicene opens a gap of 1.55 meV at the Dirac point. This band gap can be further tailored by applying in plane stress, an external electric field, chemical functionalization and defects. In this topical theoretical review, we would like to explore the electronic, magnetic and optical properties, including Raman spectroscopy of various important derivatives of monolayer and bilayer silicene (BLS) with different adatoms (doping). The magnetic properties can be tailored by chemical functionalization, such as hydrogenation and introducing vacancy into the pristine planar silicene. Apart from some universal features of optical absorption present in all these 2D materials, the study on reflectivity modulation with doping (Al and P) concentration in silicene has indicated the emergence of some strong peaks having the robust characteristic of a doped reflective surface for both polarizations of the electromagnetic (EM) field. Besides this, attempts will be made to understand the electronic properties of silicene from some simple tight-binding Hamiltonian. We also point out the importance of shape dependence and optical anisotropy properties in silicene nanodisks and establish that a zigzag trigonal possesses the maximum magnetic moment. We also suggest future directions to be explored to make the synthesis of silicene and its various derivatives viable for verification of theoretical predictions. Although this is a fairly new route, the results obtained so far from experimental and theoretical studies in understanding silicene have shown enough significant promising features to open a new direction in the silicon industry, silicon based nano-structures in spintronics and in opto-electronic devices.